Evaluation of the Effectiveness of Carbon Tax as a Tool for Controlling Air Pollution in Indonesia: Challenges and Opportunities - Abdul Wahab; Sariana Damis; Lina Mariana; Hernianti Harun; Nur Sandi Marsuni (Jurnal Riset Perpajakan: Amnesty, 2024)
The implementation of a carbon tax is increasingly recognized as an effective tool for controlling air pollution by providing economic incentives to reduce greenhouse gas emissions. This study evaluates the effectiveness of carbon tax as a pollution control tool in Indonesia, focusing on the challenges and opportunities presented by its adoption. Using a literature review approach, this research examines various secondary sources, including peer-reviewed journals, government reports, and publications from international organizations. The analysis includes thematic synthesis and comparative analysis to understand how carbon taxes have been applied globally and what lessons can be drawn for Indonesia. Results indicate that while the carbon tax presents significant potential for reducing air pollution, its success in Indonesia faces numerous challenges. Key obstacles include public resistance, regulatory complexities, economic considerations, and the readiness of industries to adapt to cleaner technologies. However, opportunities exist in aligning the carbon tax with international environmental standards, leveraging technological advancements, and increasing public awareness. Successful implementation would not only improve air quality but also support Indonesia's commitments to global climate goals. This study contributes to a deeper understanding of how Indonesia can utilize carbon tax policy effectively by addressing its unique socio-economic and regulatory landscape. Recommendations are provided for policymakers to mitigate challenges and maximize the benefits of a carbon tax as a sustainable tool for air pollution control. This analysis aims to inform strategic actions that strengthen Indonesia's environmental policies in alignment with international best practices.